Karya-Karya Hadith dalam Tulisan Jawi - Deraman, Fauzi (Jurnal Usuluddin, 1998)
The article attempts to evaluate the status and use of hadith in Kitab Jawi (Malay classical works written in Arabic transcripts) in the region of South East Asia. The coming of Islam has transformed the whole structure of the society and developed the knowledge culture of the people. Many ulama's have produced valuable works in various Islamic disciplines written in Arabic transcript which came to be known as Kitab Jawi.